The Influence of Profitability and Leverage on Stock Prices with Dividend Policy as a Moderation in Oil and Gas Subsector Companies - Fiska Noviana; Maiyaliza Maiyaliza (Asian Journal of Management Analytics, 2026)
This study examines the influence of profitability and leverage on stock prices, with dividend policy serving as a moderating variable, in oil and gas sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Employing an associative quantitative research design, the study applies purposive sampling to select nine companies, yielding a total of 45 firm-year observations. The variables analyzed comprise Return on Equity (ROE) as a proxy for profitability, Debt-to-Equity Ratio (DER) as a proxy for leverage, stock price as the dependent variable, and Dividend Payout Ratio (DPR) as a proxy for dividend policy. Data were processed using multiple linear regression and Moderated Regression Analysis (MRA) with the aid of SPSS version 25.0.